THE INFLUENCE OF PARENTING PATTERNS ON STUDENT LEARNING OUTCOMES IN CLASS V - Sirait, Esti Marlina; Pasaribu, Eva; Sijabat, Osco Parmonangan; Damanik, Efriyanti Irene (Dharmas Education Journal (DE_Journal), 2025)
This research discusses the influence of parenting patterns on student learning outcomes in class V of SD Negeri 091607 Sinaksak. The type of research used is a quantitative approach. The aim of this research is to find out how parenting styles play an important role in improving student learning outcomes in class V of SD Negeri 091607. The data that researchers have collected using validity tests, reliability tests, normality tests, homogeneity tests, and also linearity tests get good result. Besides that study This also uses the t-test and coefficient test determination . Based on the tests and analyzes that have been carried out , can obtained conclusion that , Based on analysis that has been done , then can obtained conclusion that The Influence of Parenting Patterns on Learning Outcomes Students in Class V of State Elementary School 091607 Sinaksak there is significant influence​ This done with using the t test. which shows that t -calculated value = 4.841 and t- table = 2.048 with p value =0.000. Because t-count > t- table or p< 0.05. Then seen from the coefficient calculation determination that Parental Parenting Pattern variable (X) in affecting Learning Outcomes Students (Y) amounted to 45.6%, while 54.4% was influenced by other variables that were not researched in this research.